Measuring current drug use in female sex workers and their non-commercial male partners in Mexico: Concordance between data collected from surveys versus semi-structured interviews - Palinkas, Lawrence A (Subst Use Misuse, 2015)
BACKGROUND: Self-reports are commonly used to assess prevalence and frequency of drug use, but it is unclear whether qualitative methods like semi-structured interviews are as useful at obtaining such information as quantitative surveys. OBJECTIVES: This study compared drug use occurrence and frequency using data collected from quantitative surveys and qualitative interviews. We also examined whether combining data from both sources could result in significant increases in percentages of current users and whether the concordance between the two sets of data was associated with the type of drug use, age, gender and socioeconomic status. METHODS: Self- reports of recent marijuana, heroin, crack, cocaine, crystal/methamphetamine, inhalant, and tranquilizer use were collected using both methods from a cohort of Mexican female sex workers and their non-commercial male partners (n = 82). RESULTS: Participants were significantly less likely to report marijuana, cocaine and tranquilizer use and frequency of use during the qualitative interviews than during the quantitative surveys. Agreement on frequency of drug use was excellent for crystal/methamphetamine, heroin and inhalant use, and weak for cocaine, tranquilizers and marijuana use. Older participants exhibited significantly higher concordance than younger participants in reports of marijuana and methamphetamine use. Higher monthly income was significantly associated with higher concordance in crack use but lower concordance with marijuana use. CONCLUSIONS: Although use of such data can result in an underreporting of drug use, qualitative data can be quantified in certain circumstances to triangulate and confirm the results from quantitative analyses and provide a more comprehensive view of drug use.